Pengaruh Pendapatan Asli Daerah (PAD) dan Dana Alokasi Umum (DAU) Terhadap Belanja Modal pada Kabupaten/Kota Provinsi Sumatera Barat tahun 2018-2021 - Wita Srinofril; Febryandhie Ananda (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
Capital expenditures are expenditures made in the context of capital formation, namely to increase fixed assets/inventories that provide benefits for more than one accounting period, including expenditures for maintenance costs which aim to maintain or increase the useful life, increase the capacity and quality of assets. The purpose of this study is to find out how much influence Regional Original Revenue and General Allocation Fund have on capital expenditure in 19 regencies and cities in West Sumatra for the 2018-2021 period. The sampling technique used the total sampling method and obtained as many as 76 data. Data were obtained from the Central Statistics Agency for West Sumatra Province through the website www.sumbar.bps.go.id. The analytical method used is panel data regression with the help of the E-Views application. After the Hausman-Test was carried out, it was decided to choose the Fixed Effect Model method. The results of the study show that Regional Original Income has no effect on Capital Expenditures and General Allocation Funds have a Positive Influence on Capital Expenditures.